2019
DOI: 10.1073/pnas.1901376116
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidative phosphorylation in NKT cells is essential for their survival and function

Abstract: Cellular metabolism and signaling pathways are key regulators to determine conventional T cell fate and function, but little is understood about the role of cell metabolism for natural killer T (NKT) cell survival, proliferation, and function. We found that NKT cells operate distinct metabolic programming from CD4 T cells. NKT cells are less efficient in glucose uptake than CD4 T cells with or without activation. Gene-expression data revealed that, in NKT cells, glucose is preferentially metabolized by the pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 66 publications
9
100
0
Order By: Relevance
“…NKT cells had higher levels of IDH2 in comparison to CD4 + T cells, which verifies studies that show increased levels of OXPHOS in NKT cells, important for their function 53 . Taken together, this demonstrates the ability of Met-Flow to simultaneously analyze diverse metabolic states on differential immune subpopulations.…”
Section: Discussionsupporting
confidence: 84%
“…NKT cells had higher levels of IDH2 in comparison to CD4 + T cells, which verifies studies that show increased levels of OXPHOS in NKT cells, important for their function 53 . Taken together, this demonstrates the ability of Met-Flow to simultaneously analyze diverse metabolic states on differential immune subpopulations.…”
Section: Discussionsupporting
confidence: 84%
“…In summary, our data establish Mst signaling as a molecular rheostat to tune immunological signals and cellular and metabolic programs, which coordinately regulate the differentiation and effector programming of iNKT cells. Given that terminally mature S3 iNKT cells, which can establish residency within the thymus (Berzins et al, 2006), and memory CD8 + T cells both appear to favor OXPHOS over glycolysis, these findings highlight a conserved metabolic program that allows T cells to maintain their survival and long-term persistence, but also allows for rapid functional remodeling upon reactivation (Kumar et al, 2019). Further, the impaired ability of Mst1-deficient iNKT thymocytes to enter into a quiescent state is consistent with the accumulating evidence for dysregulated Hippo pathways with human cancers (Moroishi et al, 2015; Yu et al, 2015), which may be attributed to defective quiescence programs.…”
Section: Discussionmentioning
confidence: 99%
“…Our canonical pathway analysis also demonstrated that OX40 + pDCs from the TME preferentially utilized mitochondrial OXPHOS as an energy source. This unique metabolic profile of this pDC subset draws comparisons to the recently identified energy demands of NKT cells, which also utilize OXPHOS as a vital energy source for their survival, proliferation, and cytotoxicity (34). Further investigation is needed to identify the glucose requirements of OX40 + pDCs because SLC2A1 (encodes Glut1) was one of the most upregulated DEGs in this pDC subset and compared with the pDCs from the dLNs of B16-F10-bearing mice (Supplemental Figure 4B).…”
Section: Cd8 + T Cells Compared With Controls Lacking Ox40l Pretreatmmentioning
confidence: 97%